Post-exposure recovery of Microcystis aeruginosa from nanoplastics stress: metabolic adaptation and damage resilience - Wang, Ruiping; Yue, Shizhong; Jia, Li; Tibihenda, Cevin; Huang, Pingping; Li, Zhenghua; Meng, Di (Frontiers in Marine Science, 2025)
Despite the ubiquitous distribution of nanoplastics (NPs) in global aquatic ecosystems, microbial adaptive strategies during the post-exposure period remain largely unexplored. In this study, Microcystin aeruginosa treated with 5 and 50 mg/L polystyrene (PS) for 15 days and then were transferred to PS-free medium for 15 days to study toxicology and post-exposure effects. The results showed that 5 and 50 mg/L PS inhibited algal growth, with inhibition rates of 6.82% and 9.34% at the end of exposure, respectively, while M. aeruginosa resumed growth on the fourth day of the post-exposure period. In addition, PS enhanced microcystins (MCs) biosynthesis and release in a dose-dependent manner during exposure, while phased variations were observed in MCs production and release during recovery. Transcriptome analysis revealed that 5 mg/L PS inhibited cell growth by disrupting cellular structures, inducing oxidative stress, altering lipid metabolism, and suppressing protein synthesis. These effects were largely reversible during the recovery phase, except for irreversible damage to the algal cell membrane. KEGG pathway analysis identified significant suppression of carbohydrate and energy metabolism during exposure, with subsequent reactivation during post-exposure. These findings suggest that M. aeruginosa may mitigate PS-induced oxidative stress through glucose accumulation and reduced energy expenditure.